Internal controls, labour processes and work at the Isthmus Lockstation, Rideau Canal, 1832–1854: Discipline and governmentality at a distance. (May 2022) - Bujaki, Merridee; McConomy, Bruce
The emergence of an internal control system to guide operations along the Rideau Canal beginning in 1832 is examined through analysis of a book of directives (the Order Book ) maintained by the lockmaster at the Isthmus lockstation. The Orders guided the work of the lockmaster and established general controls and control activities. Orders for adequate documents and records, physical control over assets and records, and proper authorization of activities were common. Orders are seen as efforts by British Royal Engineers, who were geographically removed from the oversight of the Rideau Canal Office, to discipline civilian lockmasters and to encourage lockmasters to govern themselves. Comparing the Order Book to Orders and Regulations in place in 1831 for the Royal Engineers also highlights similarities between expectations of Royal Engineers and those established for the civilian workforce under their direction, indicating a transfer of accounting technologies from the Royal Engineers to the civilian workforce.